Les aveux imaginaires - Aude, Nicolas (ENS Éditions, 2022)
This book examines the proliferation of self-disclosures that has occurred in European fiction since the end of the 18th century. Its object is the novelistic scene of confession as we find it represented by six authors from England, France and Russia: Ann Radcliffe, George Sand, Charlotte Brontë, Fedor Dostoyevsky, Maxime Gorki and Georges Bernanos. The comparison invites us to distance ourselves from the traditional categories of literary history. By fitting into the narrative dynamic of romantic mysteries, this scenography reveals a fundamental fragility of the division between public and private in the context of post-Romantic creation. Viewed through the prism of a cultural history of confession, such a mosaic of texts can finally resonate with the hypermodern proliferation of self-expression. The paradoxes of their imaginary confessions thus become our paradoxes.